1985
DOI: 10.1159/000249526
|View full text |Cite
|
Sign up to set email alerts
|

Paget’s Disease of the Nipple

Abstract: The most relevant literature concerning Paget’s disease of the breast is reviewed. A clinical and pathological study of female patients with Paget’s disease of the breast observed during 30 years at the Lisbon ‘Institute Português de Oncologia’ is carried out and its results are discussed. The low incidence of the disease in this series, when compared with those described in the available literature, is pointed out. The absence of a relation between the type of the cutaneous lesions and the histological type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…59 MPD can occur at any age but is more common in older patients. 60 It can arise in the setting of ipsilateral invasive carcinoma or DCIS or occur in the absence of either. Of 1704 women with MPD registered in the 1988-2002 SEER database, 50.4% had ipsilateral invasive carcinoma, 36.3% had ipsilateral DCIS, and 13.3% had MPD alone.…”
Section: Paget Disease Of the Breast Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…59 MPD can occur at any age but is more common in older patients. 60 It can arise in the setting of ipsilateral invasive carcinoma or DCIS or occur in the absence of either. Of 1704 women with MPD registered in the 1988-2002 SEER database, 50.4% had ipsilateral invasive carcinoma, 36.3% had ipsilateral DCIS, and 13.3% had MPD alone.…”
Section: Paget Disease Of the Breast Clinical Featuresmentioning
confidence: 99%
“…Analysis of 1973–2002 SEER data showed that the age-adjusted incidence rate of MPD in selected states in the United States peaked in 1985 (1.5 per 100,000-woman years) and has decreased yearly thereafter, with a 45% decrease between 1988 and 2002, likely secondary to the implementation of breast cancer screening 59 . MPD can occur at any age but is more common in older patients 60 . It can arise in the setting of ipsilateral invasive carcinoma or DCIS or occur in the absence of either.…”
Section: Paget Disease Of the Breastmentioning
confidence: 99%
“…Multiple research studies validate that approximately 50% of patients diagnosed with MPD exhibit a detectable breast mass, and 90-94% are linked to underlying invasive disease. Conversely, instances involving a lesion that lacks a discernible mass typically correlate with DCIS [1,37,39,40]. Some patients may not exhibit suggestive signs of MPD with an occasional PC finding through histopathologic NAC examination during mastectomy.…”
Section: Diagnosismentioning
confidence: 99%
“…It is common in postmenopausal women from the 5 th decade and above. Some cases have been reported in adolescents [38] .…”
Section: Types Of Premalignant and Malignant Cancers Of The Breastmentioning
confidence: 99%